JOB SATISFACTION IN THE TEXTILE INDUSTRY EMPLOYEES IN TIRPUR, INDIA - R, Kanakarathinam; Shobana, S (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Indian Textile industry is playing a major role in the development of the Indian Economy. Tamil Nadu state provides more revenue through the Textile industry in this state. Tirupur contributes more revenue collection of the Tamilnadu state. Tirupur is the "knitwear capital" of India. It has spurred up the textile industry in India for the past three decades. Jab satisfaction is one of the factors of Quality to Work Life (QWL). Better quality of QWL ultimately improves production and gets more satisfaction among the employee. Job satisfaction indicates the positive affective responses of employees to their job environment. Nowadays textile industry employees are dissatisfied with job viz., absenteeism, annoyances, anxiety, reduction in efficiency, physical pains and this is evident through many earlier types of research on several aspects of human resources in the textile industry. Hence, the researcher wants to know the job satisfaction position of textile industry employee who is working in Tirupur